Critically Endangered Fijian Crested Iguana (Brachylophus vitiensis) Shows Habitat Preference for Globally Threatened Tropical Dry Forest - Morrison, C.; Keppel, Gunnar; Thomas, N.; Rounds, I.; Harlow, P. (University of Hawaii Press, 2009)
Tropical dry forests are a unique and threatened ecosystem in the Pacific and globally. In Fiji, the endangered Fijian crested iguana (Bracbylopbus vitiensis) is endemic to tropical dry forests. Yadua Taba Island contains one of the best remaining stands of tropical dry forest in the Pacific along with the largest (and only secure) population of B. vitiensis in Fiji and has been proposed as a translocation source for iguana conservation. In this study we determined the major vegetation types on Yadua Taba and identified forest habitat preferences of B. vitiensis to (1) characterize the island's habitats for tropical dry forest regeneration monitoring and (2) understand which forest types are preferred by iguanas for future translocation projects. Vegetation data were collected using reconnaissance, entitation, line transects, and aerial photos. Iguana abundance data were collected by nocturnal surveys of permanent transects. Six major vegetation types were identified of which tropical dry forest was the largest (46% of the island), followed by a combination of rocky cliff-shrubland/grassland vegetation (26%). Our conservative estimate of B. vitiensis population size on Yadua Taba is 12,000 iguanas, the majority of which occur in tropical dry forest. Superabundance of the dry forest understory tree Vavaea amicorum, the favorite fruit species of iguanas, may help account for the high density of iguanas observed.These results highlight the ecological link between tropical dry forest and B. vitiensis and emphasize the importance of rehabilitation or conservation of tropical dry forest habitat in potential iguana translocation sites as part of the management plan for B. vitiensis throughout the Fiji Islands.